2010
DOI: 10.1111/j.1755-0998.2010.02877.x
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding aphids (Hemiptera: Aphididae) of the Korean Peninsula: updating the global data set

Abstract: DNA barcode (mitochondrial COI) sequences are provided for species identification of aphids from the Korean Peninsula. Most (98%) of the 154 species had distinct COI sequences (average 0.05% intraspecific pairwise divergence) relative to the degree of sequence divergence among species (average value 5.84%). For species in common with other regions, barcodes for Korean samples fell near or within known levels of variation. Based on these results, we conclude that DNA barcodes can provide an effective tool for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 25 publications
9
95
0
1
Order By: Relevance
“…CO-1 is used as bar coding gene for elucidation of cryptic aphid species of order Hemiptera (Rebijith et al, 2013). CO-I gene sequence as DNA barcoding is highly reported as effective tool for species identification (Foottit et al, 2008;Glover et al, 2010;Lee et al, 2010). In addition, CO-I may be suitably employed to elucidate the prevalence of biotypes and for the discovery of new species within the Aphididae (Shufran et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…CO-1 is used as bar coding gene for elucidation of cryptic aphid species of order Hemiptera (Rebijith et al, 2013). CO-I gene sequence as DNA barcoding is highly reported as effective tool for species identification (Foottit et al, 2008;Glover et al, 2010;Lee et al, 2010). In addition, CO-I may be suitably employed to elucidate the prevalence of biotypes and for the discovery of new species within the Aphididae (Shufran et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed similar average intraspecific pairwise R. padi sample divergence (0.61%), although the range was larger: 0.00-2.49%. Generally, based on the global data set (Foottit et al 2008;Lee et al 2011), the average genetic divergence of COI barcode sequences within aphid species was reported to be 0.05% (range 0.00-1.00%). Such a low values of divergence are explainable by modest numbers of sequences used by the above reported analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Such a low values of divergence are explainable by modest numbers of sequences used by the above reported analyses. Namely, Foottit et al (2008) exploited three, whilst Lee et al (2011) eight sequences of R. padi when compared to 44 used in our study. Out of 20 partial COI sequences of R. nymphaeae, six COI haplotypes were identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, morphological examination of thrips to species requires adult specimens as there are no reliable keys for identification of immature stages, but even these are often difficult for a non-expert to use. In this regard, DNA barcoding can be an added advantage and an effective tool for molecular species identification (Brunner et al 2004;Glover et al 2010; Lee et al 2010), elucidation of biotypes or cryptic species, and host associated genetic differences (Shufran et al 2000;Brunner et al 2004) and species discovery in insects. Additionally, DNA barcoding could also be used in the identification of unknown thrips species that co-exist in a cropping system, since one particular Tospovirus disease may sometimes be vectored by more than one species of thrips (Wijkamp et al 1995;Kadirvel et al 2013;Amin et al 1981).…”
Section: Advantages Of Dna Barcoding In Taxonomymentioning
confidence: 99%